Instructions to a statesman. Humbly inscribed to the Right Honourable George Earl Temple. [By W. Godwin] (Scholars' Facsimiles & Reprints, 1966)
Photomechanical reprint of the ed.: London, Murray etc., 1784. In: W. Godwin, Four early pamphlets (1783-1784).